Scaling Up and Integrating Effective Behavioral and Instructional Support Systems (EBISS): A Study of One State's Professional Development Efforts. (February 2020) - Chaparro, Erin A.; Smolkowski, Keith; Jackson, Kathleen Ryan
Oregon's Effective Behavioral and Instructional Support Systems (EBISS) initiative was implemented in 25 school districts. The initiative trained and coached district leaders and teachers in the use of the EBISS model through the lens of implementation science. The EBISS model integrates school-wide positive behavior intervention and supports (SWPBIS) and the school-wide reading model (SWRM) to improve schools for all students and to reduce the number of students at risk of learning difficulties. Proximal outcomes included gains in the number of building-level SWPBIS and SWRM implementation teams and the activities of those teams. Distal outcomes included statistically significant gains in oral reading fluency (ORF) in first and third grades and marginally significant decreases in the percentage of students in the intensive category for reading in second and fourth grades. These findings suggest that to optimize improvements in teacher and student outcomes, a rigorous system of professional development and coaching appears necessary.